DANA ALOKASI UMUM (DAU) DAN KETERGANTUNGAN FISKAL DAERAH - Didik Susetyo (Department of Development Economics, Universitas Sriwijaya, 2007)
This article discussed the function and formula of block grants in Indonesia. The general block grants called ‘Dana Alokasi Umum' (DAU) in Indonesia faced many problems, such as the goodness of fit the formula, the principle of goals, and local dependency. The impact of DAU to the local budget can be seen two different functions: (1) improve the capability of local finance; (2) increase the fiscal dependency. Both impacts tend to face ‘trade-off' in implementation. However, fiscal dependency is an indication that local government depend to transfer of fund from central government. Finally, DAU support local budget where as DAU also increase the dependency. Re-formulation of DAU can elaborate the differences of local satisfaction and local fiscal dependency. Keywords: general block grant, fiscal dependency